Multicultural Education Management Based on the Life Character of Siblings - Pattipeilohy, Poltjes; Cindy, Agustin Hanivia; Pattiasina, Johan (Global Education Journal, 2025)
The background of this research begins with social life in Ambon City which has various ethnicities, religions, and cultures. This diversity often becomes a challenge as well as an opportunity in the world of education. SMA Negeri 3 Ambon is one of the schools that stands out because it prioritizes the local value of "sibling life" in the management of multicultural education. The purpose of this study is to describe the implementation of multicultural education management based on the character of sibling life at SMA Negeri 3 Ambon. The research method used is a qualitative approach with case studies. Data collection was carried out through in-depth interviews, participatory observation, and documentation. The results of the study show that education management at SMA Negeri 3 Ambon integrates the values ​​of sibling life into school policies, student behavioral habits, and also curriculum development and extracurricular activities. Values ​​such as mutual respect, tolerance, and solidarity are part of the school culture and help strengthen relationships between school residents. In conclusion, multicultural education management based on local character at SMA Negeri 3 Ambon has succeeded in creating a harmonious, inclusive, and character-based learning atmosphere and is an example of appropriate education in a diverse society.